A pragmatic orthotropic elasticity-based damage model with spatially distributed properties applied to short glass-fibre reinforced polymers. (November 2021) - Holmström, Petter Henrik; Clausen, Arild Holm; Berstad, Torodd; Morin, David; Hopperstad, Odd Sture
Abstract: This article presents a simple progressive damage model for quasi-brittle materials, combining orthotropic elasticity with a scalar damage model including spatial variation of the damage initiation strain and the crack band method for softening regularization. The model's performance is first analyzed from a numerical point of view and then demonstrated for tensile tests ( 0 °, 45 ° and 90 ° ), open-hole tensile tests ( 0 ° ) and three-point bending ( 0 ° and 90 ° ) tests of short fibre-reinforced polypropylene with 15 wt.% and 30 wt.% glass fibres. Despite its simplicity, the model captures the anisotropic elastic and inelastic behaviour observed in experiments. The model is applicable for orthotropic brittle or quasi-brittle materials, where the variability in elastic properties is negligible and the orientation dependency of the fracture strain is small or not relevant for the application.